2014
DOI: 10.1186/1471-2458-14-1132
|View full text |Cite
|
Sign up to set email alerts
|

Impact of implementing performance-based financing on childhood malnutrition in Rwanda

Abstract: BackgroundMalnutrition remains a serious concern in Rwanda, particularly among children under-5 years. Performance-based financing (PBF), an innovative health systems financing strategy, has been implemented at the national level since 2008. This study aimed to assess the impact of PBF and other factors associated with the prevalence of three classifications of malnutrition (stunting, wasting and underweight) in children under-5 years in Rwanda.MethodsThe study is a cross-sectional study comprising of 713 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
14
0
2
Order By: Relevance
“…The HIV program particularly benefited from the implementation of PBF, since payments were given for several key HIV care indicators, including the number of new adults and infants on ART, the number of HIV-positive pregnant mothers put on ART during pregnancy, and the number of HIV patients who receive a CD4 test in accordance with national guidelines. The program has been shown to have an effect on several health outcomes and it continues to be empirically evaluated and discussed in the literature [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HIV program particularly benefited from the implementation of PBF, since payments were given for several key HIV care indicators, including the number of new adults and infants on ART, the number of HIV-positive pregnant mothers put on ART during pregnancy, and the number of HIV patients who receive a CD4 test in accordance with national guidelines. The program has been shown to have an effect on several health outcomes and it continues to be empirically evaluated and discussed in the literature [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…35 In the same year, pay-for-performance was scaled up at the national level to improve the quality of care provided by health facilities. 29 In 2009, the National Protocol on Management of Malnutrition was enacted in health facilities and the National Emergency Program to Eliminate Malnutrition (NEPEM) was launched to eliminate all forms of undernutrition in Rwanda, especially stunting, with a community-based nutritional intervention approach. 49 Children aged 6 to 24 months in the RDHS 2010 survey (born in 2008 or later) could enjoy the increased and improved nutrition care provided by rural health centers during their critical window of opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…19,28 A few studies have discussed the possible link between Mutuelles enrollment and health outcomes, but without supporting empirical evidence. 29,30 In this study, taking advantage of the 2010 Rwanda Demographic and Health Survey (RDHS 2010) and the 2010 District Health System Strengthening Tool (DHHST), we determined the availability of nutritional services in the MSP of Mutuelles across rural health centers in Rwanda and conducted the first empirical study at the individual level that quantifies the association between Mutuelles enrollment and the likelihood of being stunted for rural children.…”
mentioning
confidence: 99%
“…Under this model of PBF, payment was made directly to health facilities based on progress toward achieving pre-determined targets to incentivize health providers as well as reward successful health centers with resources for further improving infrastructure and operations. A number of studies have demonstrated positive impacts of this strategy, such as increased uptake of maternal and child health services (911). …”
Section: Introductionmentioning
confidence: 99%